2018
DOI: 10.1007/s00442-018-4087-5
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical variation in treetops: causes and consequences for tree-insect herbivore interactions

Abstract: The interaction of plants and their herbivorous opponents has shaped the evolution of an intricate network of defences and counter-defences for millions of years. The result is an astounding diversity of phytochemicals and plant strategies to fight and survive. Trees are specifically challenged to resist the plethora of abiotic and biotic stresses due to their dimension and longevity. Here, we review the recent literature on the consequences of phytochemical variation in trees on insect–tree–herbivore interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 91 publications
1
52
0
Order By: Relevance
“…This finding corresponds well with previous work (Barbour et al., , ; Johnson, Agrawal, Maron, & Salminen, ) and a meta‐analysis of heritability estimates for plant functional traits (Geber & Griffen, ), which found that plant secondary chemistry was more heritable than plant growth and size metrics ( h 2 = 0.43 and 0.16, respectively). Secondary metabolites mediate plant interactions with the environment and thus often undergo variable selection pressures across space and time, resulting in highly variable expression across plant genets (Lämke & Unsicker, ; Moore, Andrew, Külheim, & Foley, ). This broad pattern is seen in levels of salicinoids and condensed tannins in Salicaceae species, which can vary up to 10‐fold across genets grown in a common location (Boeckler et al., ; Förster, Ulrichs, Zander, Kätzel, & Mewis, ; Lindroth & St. Clair, ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding corresponds well with previous work (Barbour et al., , ; Johnson, Agrawal, Maron, & Salminen, ) and a meta‐analysis of heritability estimates for plant functional traits (Geber & Griffen, ), which found that plant secondary chemistry was more heritable than plant growth and size metrics ( h 2 = 0.43 and 0.16, respectively). Secondary metabolites mediate plant interactions with the environment and thus often undergo variable selection pressures across space and time, resulting in highly variable expression across plant genets (Lämke & Unsicker, ; Moore, Andrew, Külheim, & Foley, ). This broad pattern is seen in levels of salicinoids and condensed tannins in Salicaceae species, which can vary up to 10‐fold across genets grown in a common location (Boeckler et al., ; Förster, Ulrichs, Zander, Kätzel, & Mewis, ; Lindroth & St. Clair, ).…”
Section: Discussionmentioning
confidence: 99%
“…In various temperate trees, temperature, water availability and herbivory are major factors causing changes in concentrations of volatile organic compounds and phenolics, as reviewed by Lämke and Unsicker (2018). In contrast to temperate trees, induction by herbivores seems to be of less relevance in expanding leaves of neotropical trees, where only phenolics slightly increase after herbivore damage (Coley et al 2018).…”
Section: Extrinsic Mechanisms Underlying Withinand Among-plant Variationmentioning
confidence: 99%
“…Lämke and Unsicker (2018) indicate that genome duplication, followed by functional diversification as well as hybridization are major drivers of variation. Coley et al (2018) review and integrate their years of research on Inga, a speciose genus of tropical trees.…”
Section: Drivers Of Plant Variationmentioning
confidence: 99%
See 2 more Smart Citations